Congenital hypothyroidism: a case report - Anak A Maswiryati; Nyoman Westra (Indonesian Pediatric Society, 2003)
Hypothyroidism resulted from deficiency ofthyroid hormone production due to adefect in thyroid gland. The disorder maybe manifested earlier. When symptomsoccur after a period of normal function of thyroid gland,the disorder may be either truly â€œacquiredâ€ or onlyappear as a variety of congenital defects in which themanifestation of the deficiency is delayed. Normal levelof triiodothyronine (T3) in children is 100-260 ng/dl,thyroxin (T4) 7.3 - 15 mg/dl and thyroid-stimulatinghormone (TSH) 2-10 mU/mL. 1,2 The age at whichsymptoms appear depends on the impairment degreeof thyroid function. In many cases, the deficiency ofthyroid hormone is severe, and symptoms tend todevelop in the early weeks of life. 1,3 The prevalence ofcongenital hypothyroidism has been found to be 1 in4,000 infants world wide; it is lower in Japan (1 in 5,500infants) and in African American population (1 in32,000 infants). Most infants with congenitalhypothyroidism are asymptomatic at birth, even whenthere is a complete agenesis of the thyroid gland. 1,3 Butin other cases, during the first few months of life, thesymptoms of hypothyroidism such as feeding problems,failure to thrive, constipation, hoarse cry, andsomnolence usually can be found. 1,3,4 The purpose ofthis study is to report a case of congenital hypothyroidismin a 14 months old child.